(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper deals with the design of home automation controlling of home appliances using wireless remote control. This is achieved using a Bluetooth module and an android application. This low-cost system can be accessed remotely using a laptop or smartphone with a software or an application installed in it. Even the elderly or disabled at home can be able to access it, making their work easy and simple. The design is very simple using some low-cost electrical apparatus, with ease of installation and smart home system also provides more safety control over the electrical switches with some power saving methods. Smart home or home automation provides a better standard of living at home with low-cost design and a user friendly interface